Schwann cell survival mediated by the signaling phospholipid lysophosphatidic acid - Weiner, Joshua A. (The National Academy of Sciences, 1999)
Lysophosphatidic acid (LPA) is a bioactive phospholipid with properties of an extracellular growth factor for many cell lines, including those derived from neuroblastomas. However, the relevance of LPA signaling to the normal, developing nervous system is unknown, in part reflecting the previous unavailability of cloned receptor genes. Recent studies of the first such gene, encoding the G protein-coupled receptor LP(A1)/VZG-1 (lysophospholipid receptor A1/ventricular zone gene-1), revealed a major locus of expression in oligodendrocytes and Schwann cells (SCs) during development, suggesting an influence of LPA on these myelinating cells. Here we report that LPA (≥10 nM) is a potent survival factor for cultured neonatal SCs, with survival activity equaling the maximal effect of neuregulin, the major peptide SC survival factor. LPA activates a pharmacologically defined signaling pathway in SCs, involving G(i) and phosphoinositide 3-kinase. Moreover, LPA’s effect depends on Akt, a downstream kinase that can mediate phosphoinositide 3-kinase-dependent survival, as demonstrated by both Western blot and transfection analyses. Overexpression of functional epitope-tagged LP(A1)/VZG-1 protein decreases SC apoptosis in response to serum withdrawal. These data demonstrate a role for extracellular LPA and its receptor LP(A1)/VZG-1 in SC survival and, more broadly, implicate G protein-coupled receptor-mediated lysophospholipid signaling as a significant mechanism in neural development.